ANALISIS PENGENDALIAN KUALITAS PRODUK PADA PROSES PERAKITAN HANDPHONE MENGGUNAKAN METODE STATISTICAL QUALITY CONTROL PADA PT SAT NUSAPERSADA TBK: ANALISIS PENGENDALIAN KUALITAS PRODUK PADA PROSES PERAKITAN HANDPHONE MENGGUNAKAN METODE STATISTICAL QUALITY CONTROL PADA PT SAT NUSAPERSADA TBK - Lim, Hartono; Azharman, Zefri (Computer Science and Industrial Engineering, 2019)
The background of this research is based on the growing growth of business competition in the electronic sector that requires quality control to be able to survive in competition, encouraging researchers to examine whether PT Sat Nusapersada Tbk has carried out the quality control process well. The purpose of this study is to analyze the implementation of quality control, types of damage, and factors that cause damage in the process of handphone assembly at PT Sat Nusapersada, Tbk. Data collection techniques carried out by interview, observation and documentation. In processing the data this research uses Statistical Quality Control (SQC) methods, namely checking sheets, histograms, control charts p, pareto diagrams, and causal diagrams. The results of data analysis and discussion show that the process of assembling mobile phones in a state of uncontrolled or still experiencing irregularities. Based on the histogram diagram, it can be concluded that the type of damage that occurred at PT Sat Nusapersada, Tbk in Batam City was damage to the camera with 992 pcs or 40.46%, damage to the microphone with 847 pcs or 34.54% and damage to the battery with 613 pcs or 25% . Factors that cause damage to the mobile assembly are workers who are less focused and inaccurate, wrong assembly methods, raw materials that are easily dirty and equipment settings that do not fit properly.